2021
DOI: 10.2196/29062
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the ROX Index in Predicting Intubation for Patients With COVID-19–Related Hypoxemic Respiratory Failure Receiving High-Flow Nasal Therapy: Retrospective Cohort Study

Abstract: Background The use of high-flow nasal therapy (HFNT) to treat COVID-19 pneumonia has been greatly debated around the world due to concerns about increased health care worker transmission and delays in invasive mechanical ventilation (IMV). Herein, we analyzed the utility of the noninvasive ROX (ratio of oxygen saturation) index to predict the need for and timing of IMV. Objective This study aimed to assess whether the ROX index can be a useful score to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
4
7
1
2
Order By: Relevance
“…Additionally, an ROX greater than 4.88 measured at 2 h after HFNC initiation had a significant association with a lower risk for intubation [ 12 ]. In line with the findings of the retrospective cohort study involving 129 patients with COVID-19 pneumonia conducted by Patel M et al [ 13 ], the study indicated that an ROX index value of less than 5 at the initiation of HFNC suggested a progression to invasive mechanical ventilation (odds ratio 2.137, P = .052). Furthermore, any subsequent decrease in the ROX index value after HFNC initiation was predictive of intubation (OR 14.67, P < .001).…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, an ROX greater than 4.88 measured at 2 h after HFNC initiation had a significant association with a lower risk for intubation [ 12 ]. In line with the findings of the retrospective cohort study involving 129 patients with COVID-19 pneumonia conducted by Patel M et al [ 13 ], the study indicated that an ROX index value of less than 5 at the initiation of HFNC suggested a progression to invasive mechanical ventilation (odds ratio 2.137, P = .052). Furthermore, any subsequent decrease in the ROX index value after HFNC initiation was predictive of intubation (OR 14.67, P < .001).…”
Section: Discussionsupporting
confidence: 78%
“…The ROX index is a simple scoring system devised to predict the failure of HFNO in acute hypoxemic respiratory failure [ 5 ]; it has shown utility in not just predicting intubation in COVID-19, but also the need for hospital admission [ 19 ]. Patel et al [ 20 ] studied the utility of the ROX index in predicting the need for IMV in COVID-19 pneumonia patients and found that a score <5 at initiation predicted the need for IMV (odds ratio [OR], 2.137; P=0.052) . The mean time to intubation was 2.5 days with 47% mortality in patients requiring IMV.…”
Section: Discussionmentioning
confidence: 99%
“…This paper [ 1 ] is an important resource for the use of high-flow nasal cannula in patients with COVID-19 and provides important insights on the current COVID-19 pandemic. Respiratory support for patients with COVID-19 is an important topic for critical patients.…”
Section: Round 1 Reviewmentioning
confidence: 99%